Development evaluation of digital education: Development evaluation of digital education - Ismoilova, Feruza (Журнал иностранных языков и лингвистики, 2022)
On the face of the twenty first century, it seems to me there is no other way of linguistic acquisition as a non-native speaker in both convenient and comprehensible avenue, but The Internet Based Education (IBE). As our live is being computerized day by day, the day of replacement of modern technologies with traditional way of educating is not far away. While being the sufficient method of teaching and learning it has also side effects for building successful teaching and learning environment. In this article, I want to share my research findings on the topic.